(untitled) (Bangladesh Medical Journal, 2016)
Transfusion of blood and blood components saved millions of lives each year. In most developing countries, however, preventable deaths still occur due to inadequate supply of safe blood and blood components which can be minimize by blood donation. In Bangladesh the annual demand for blood transfusion is estimated to be 2,00,000 to 2,50,000 unit per year. But due to lack of voluntary donor and consciousness among people this demand is hardly met. Because blood donors are altruistic volunteers, they should be protected as much as possible by the pre-donation counseling. This prospective observational study was carried out in the department of transfusion medicine in Bangabandhu Sheikh Mujib Medical University from February 2010 to january 2011 with the intention to see the immediate adverse reactions after blood donation. 1,500 patients were selected consecutively after considering inclusion and exclusion criteria. Adverse reaction were observed during and 30 minutes following blood donation. Among the total 1500 respondents, 394 cases experienced adverse effects of blood donation namely; vertigo (9.7%), sweating and warmness (5.0%), bruising (3.0%), nausea (6.3%) and fainting (2.3%). careful monitoring of all blood donors after donation and counseling of adverse effect before donation is important. Bangladesh Med J. 2016 May; 45 (2): 75-78